Realizacja misji nauczycielskiej Kościoła w publicznych stowarzyszeniach wiernych związanych z "Towarzystwem Św. Franciszka Salezego" - Domaszk, Arkadiusz (Prawo Kanoniczne, 2011)
The right for the Faithful to associate exist in the canon law. Among the public associations of the Christian Faithful there are also those, which are related to spirituality of certain religious institutes. The aim of this work was to elucidate and analyze public associations of the Christian Faithful, which are connected with the Society of St. Francis de Sales, as well as the question of how those associations accomplish the teaching mission of the Church. In the beginning the most important canon law norms concerning the public associations of the Christian Faithful has been mentioned. St. John Bosco established three groups of the Faithful, viz. Salesians collaborators, worshippers of Mary Help of Christians and Salesian former pupils. The St. John of Bosko’s thought has been constantly fulfilled in further development of Salesian charism. A constant development of Salesians Collaborators Association is being observed. The association fulfills its own evangelistic and educational mission, and being at the same time a public association in the Church- it does it in the name of the Church. Also the Mary Help of Christian Association is a public association of the Faithful. Its important trait is to spread the Marian cult, especially the call of Mary Help of Christian. That assignment, together with prayer makes up the evangelistic mission. The next important group connected with the Salesian charism is a confederation of associations of Salesian former pupils. It is the case of federation of associations rather than of one organizationally close entity. Undoubtedly, the confederation continues and expands Salesians’ educational work and essentially makes up the educational assignments of the Church. At once it has to be said that the confederation is not a public association of the Faithful, because its members are also the Christians belonging to other Churches and communities, and also non-Christian people. The group Volunteers with the St. John of Bosco is also the public association of the Faithful. There is a place for many different groups and communities in the family of Salesians; a part of them exist in the form of private associations of the Faithful. While reviewing the associations related to Salesian Congregation the following picture could be used. The seed sowed by the Salesian founder grew large. Each new group, movement or association becomes another bough. Each of it refers to the Salesian charism, which also stands for joining in evangelistic and educational assignments, mainly directed to youth and popular environments.